Unipolar depressive disorders. (November 2016) - Symonds, Catherine; Anderson, Ian M.
Abstract: Depression is a common relapsing mood disorder that causes significant distress and impairment in social and occupational functioning. It is associated with an increased risk of death, not only through suicide, but also from physical illnesses such as cardiovascular disease. It is under-recognized and undertreated and should be considered in individuals at high risk of depression, for example those suffering from chronic physical health problems. Its aetiology is multifactorial, and co-morbidity with other psychiatric disorders is common. Assessment of depression requires an assessment of the duration, symptom severity, suicide risk and functional impairment of the current episode, co-morbid diagnoses, past mood and treatment history, and developmental, social and family history. Treatment is guided by illness severity, presentation and prior history. It includes psychosocial interventions, medications and their combination, with antidepressant medication reserved for persistent and moderate to severe depression. Prevention of relapse is a priority; risk factors for this should be assessed and used to guide the choice of prophylactic drug and psychological treatment.